KEBIJAKAN PERLINDUNGAN KEBERADAAN PASAR TRADISIONAL DAN UMKM (STUDI PERATURAN BUPATI NOMOR 25 TAHUN 2011 DI KABUPATEN KULON PROGO) - , NURYANI, Dr. Erwan Agus Purwanto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this research was to determine the effectiveness of the arrangement of modern stores in an effort to protect traditional markets and Micro, Small and Medium Enterprises (UMKM) in the Kulonprogo Regency. In an effort to protect traditional markets and UMKM in the Kulonprogo Regency, Kulonprogo Regency Government has issued âPeraturan Bupati Kulon Progo Nomor 25 Tahun 2011â About Arrangement Traditional Markets, Shopping Centers and Modern Stores. The background of this research is the growth minimarket in the Kulonprogo Regency especially Alfamart and Indomart very rapidly and some of these minimarket distance is very close to traditional markets as well as UMKM. The research method used in this research is a qualitative descriptive with method of data collection is participant observation, semi-structured interviews, documentation. Logical theoretical framework in this research is with the development of modern stores very rapidly, the government needs to protect traditional markets and UMKM for the markets to stay alive and walking hand in hand. Based on the discussion of the results obtained as following conclusions: 1. The presence Indomart and Alfamart in the Regency Kulonprogo very disturbing traders in traditional markets as well as UMKM, especially Alfamart and Indomart distance with the traditional markets as well as UMKM are very close together. 2. The policy of the arrangement of modern stores is in the formâPeraturan Bupati Kulon Progo Nomor 25 Tahun 2011â in an effort to protect traditional markets and Micro, Small and Medium Enterprises (UMKM) in the Kulonprogo Regency is not effective because of a failure of policy implementation. 3. At the present time this has been a shift tendency for people in choosing where to shop, especially when shopping for groceries. 4. Some consumers are still shopping âsembakoâ in the mini market despite a greater distance from home on the grounds as it can be an empty shop in accordance with the time they have, do not collide with the hours of work, can use a debit card so no need to carry cash, a comfortable and clean place to shop. Based on these conclusions the authors present the following recommendations: 1. Local governments create policies that protect small traders by restricting of minimarket and controlling to permit the establishment of mini market. 2. Policies that have been created in order to be implemented with full commitment and consistent, and necessary support resources. 3. Government guide the trader to change the paradigm of thinking associated with the merchant attempts to attract consumers. 4. Local governments need to change the system to be sold in traditional markets such as the mini market that will facilitate sellers and buyers in shopping.